Flight investigation of blended command model in low speed maneuvering - Jeram, G. (My University, 2022)
This piloted flight investigation with an UH-60 utility helicopter assessed the handling qualities of a blended command response-type alongside attitude command and rate command response-types in longitudinal and lateral axes with three low speed Mission Task Elements (MTEs) of Aeronautical Design Standard ADS-33E-PRF. The Blended Command Model produces an Attitude Response-Type when the cyclic is near center, produces a Rate Response-Type when the cyclic is distant from center, and produces a blended response at intermediate displacements. The investigation assessed three variations of blended command vis-à-vis proportional attitude and rate commands with the Hover, Depart Abort, and Lateral Reposition MTEs. Among the five options, the evaluation pilots ranked blended command best in a Good Visual Environment by an average of 0.5 better than the second ranked attitude command using the Cooper Harper scale. The pilots assessed blended command second best under a Degraded Visual Environment by an average 0.3 worse than the top-ranked attitude command.